Deep Eutectic Solvent Assisted Dispersion of Carbon Nanotubes in Water - Zaib, Qammer; Adeyemi, Idowu; Warsinger, David M.; AlNashef, Inas M. (Frontiers in Chemistry, 2020)
Deep Eutectic Solvents (DESs) are emerging as a promising medium for many chemical processes. They can be used to observe specific properties required for nanomaterials’ applications. Controlled CO2 adsorption requires disaggregation of carbon nanotubes into smaller bundles which can be accomplished by dispersing them in aqueous DES system. In this study, response surface methodology (RSM) was adopted to examine the impacts of three important factors on the dispersion of single walled carbon nanotubes (SWNTs) in Choline Chloride-Glycerol (ChCl-Gly); (i) ChCl-Gly (mass % in water), (ii) sonication energy input (J/mL), and (iii) SWNTs’ concentration (mg/L). The net negative surface charge of ChCl-Gly, a leading DES, provided superior dispersion of inherently negatively charged SWNTs in water via electrostatic repulsion. The statistical approaches used for the optimization of the dispersion was not known to be previously applied to such systems. The impacts of the dispersion factors were quantified by the average aggregate diameter (nm) and polydispersity (polydispersity index, PDI) of SWNTs in aqueous-DES systems. Models were developed, experimentally verified, and statistically validated to map the impacts of these factors and to obtain optimized dispersions. The optimized dispersions, characterized by the small (< 100 nm) and uniform (< 0.1 PDI) SWNTs’ aggregates, were achieved at lower sonication energy costs which can have promising implications across many nano-manufacturing fields. The dispersion/aggregation mechanism was proposed using COSMO-RS (based on equilibrium thermodynamics and quantum chemistry) modeling of ChCl-Gly and zeta potential measurements of SWNTs. This understanding will help create optimally sustainable and economically feasible DES-nanomaterial dispersions.